Pengaruh Orientasi Pelayanan Terhadap Komitmen Organisasi Pada Tenaga Non Medis Di Rumah Sakit X Surabaya - Cahyani, Tarisa Pramesti Tirta; Kurniawan, Afif; Tjokro, Silvia Haniwijaya (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Understanding customer needs and customer desires by providing the best quality service, it makes many hospitals stand up to meet customer needs by providing optimal service. So that management must provide the best service so that hospital can be recognized by the comunity. Service orientation can be carried out by human resources which are very valuable assets, service orientation can be measured by employee commitment to their organization. Because employees who have a commitment to their organization will continue to maintain the duties and responsibilities. Aims: The study aims to analyze the influence of service orientation towards organizational commitment at hospital X Surabaya. Methods: The study use a quantitative research design with a tpopulation of 171 and sample of 68 respondents. The research variables consist of : the influence of service orientation (independent) and organizational commitment (dependen) Results: The results showed that influence service orientation organizational commitment in non medical staffs at Hospital X Surabaya with p value (sig) of 0.000 below 0.05. The result of statistical processing show the ability of 71.4% of the service orientation variable to influence organizational commitment to non medical. . Conclusion: Service orientation has influence on organizational commitment hospital X Surabaya. This can occur because orientation is given to customers as a guide for employees in carrying out the task and responsibilities given and building a work culture and a conducive atmosphere in the hospital. Aims: The study aims to determine the influence of service orientation on organizational commitment at hospital X Surabaya. Methods: The study use a quantitative research design with a type of research used in a planned and structured manner with the use of many numbers from data collection, processing so it can produce a result. The research variables consist of : the influence of service orientation (independent) anda organizational commitment (dependen) Results: The result of the study indicate that service orientation influence organizational commitment to non medical at Hospital X Surabaya with a Tvalue of 7.464 and p value (sig) of 0.000 below 5%. The result of statistical processing indicate the ability of 71.4% of the service oreinetation variable to inlunfluence organizational commitment to non medical. . Conclusion: Service orientation has influence on organizational commitment hospital X Surabaya. This can occur because orientation is given to customers as a guide for employees in carrying out the task and responsibilitys given and building a work culture and a conducive atmosphere in the hospital.